The ethics of straight-thinking and euthyphronics - Nierodka, Paweł (Folia Philosophica, 2008)
The questions the author searches the answers to concern, among other things, the relationship between euthyphronics and ethics of straight-thinking and the issue of therapy. It was looked at in a broader way, i.e. not only in reference to euthyphronics or ethics of straight-thinking, but also recentivism. From the perspective of euthyphronics, it is not only about rejecting a technique, but nivelling its negative influence, showing people ways of protecting a „mental environment”, and being against the idea of leaving life wisdom aside at the expense of knowledge. In this way, euthyphronics refers to other sciences about man, and, among others, to the ethics of euthyphronics as its axiological basis.